Assessment of safety and tolerability of remogliflozin etabonate (GSK189075) when administered with total daily dose of 2000 mg of metformin - Robert Dobbins; Elizabeth K. Hussey; Robin O'Connor-Semmes; Susan Andrews; Wenli Tao; William O. Wilkison; Bentley Cheatham; Katare Sagar; Barkate Hanmant (BMC, 2021)
Abstract Background Patients with type 2 diabetes mellitus (T2DM) are characterized by an elevated glycemic index and are at a higher risk for complications such as cardiovascular disease, nephropathy, retinopathy and peripheral neuropathy. Normalization of glycemic index can be achieved by dosing combinations of metformin with other anti-diabetic drugs. The present study (Clintrials number NCT00519480) was conducted to evaluate the safety, tolerability, pharmacokinetics and pharmacodynamics of remogliflozinetabonate, an SGLT2 inhibitor, withdoses (500 mg and 750 mg BID) greater than the commercial dose (100 mg BID)in combination with metformin with minimum daily dose of 2000 mg given in two divided doses. Methods This was a randomized, double-blinded, repeat dose study in 50 subjects with T2DM. The study was conducted in three phases; run-in, randomization, and treatment. All subjects were on a stable metformin dosing regimen. Cohort 1 subjects were randomly allocated to receive either remogliflozin etabonate 500 mg BID or placebo BID (2:1) in addition to metformin. Cohort 2 subjects were administered with either remogliflozin etabonate 750 mg BID or placebo BID (2:1) in addition to metformin for 13 days. All the subjects were assessed for safety (adverse events, lactic acid levels, vital signs, electrocardiogram [ECG]), pharmacokinetic evaluation, and pharmacodynamics (Oral Glucose Tolerance Testing) parameters. Results Co-administration of remogliflozin etabonate and metformin was well tolerated in all subjects during the observation period. There were no severe or serious adverse events (SAEs) and no increase in lactic acid concentration was reported during the study. The statistical results showed that concomitant administration of remogliflozin etabonate, either 500 mg or 750 mg BID, with metformin had no effect on the pharmacokinetics of metformin. The accumulation ratios, Day 13 vs. Day 1, for AUC values of remogliflozin etabonate and its metabolites were all very close to 1, indicating no accumulation in plasma concentrations of remogliflozin etabonate and its metabolites. Mean glucose values from baseline and glucose and insulin values following oral glucose tolerance test (OGTT) were decreased in all treatment groups. Conclusion Co-administration of doses of remogliflozin etabonate (500 mg BID or 750 mg BID) greater than the commercial dose (100 mg BID) with metformin (2000 mg BID) was shown to be safe and effective during the observation period. Trial registration ClinicalTrials.gov , NCT00519480 . Registered:22 August 2007.